Hubungan ASI Eksklusif dengan Kejadian Stunting pada Balita 6-24 Bulan - Sudirman, Nurul Aisyah; Utami Murti Pratiwi; Andi Irhamnia Sakinah; Purnamaniswaty Yunus (Alami Journal (Alauddin Islamic Medical) Journal, 2024)
Stunting is currently still a problem in Makassar. Incidence stunting from Riskesdas data in Makassar is 25.9% and stunting data at Kassi Kassi Health Center is 22.92%, this figure is still above the stunting limit according to World Health Organization, which is 20%. One of the causes of stunting is mainly influenced by nutritional intake, exclusive breastfeeding for six months because breast milk is needed during the growth period. The purpose of this study was to determine the relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 6-24 months. The research design used was observational analytic with a cross-sectional approach. This research was conducted in the working area of the Kassi Kassi Health Center from November to December 2021. The sampling technique used was purposive sampling. A total of 90 samples in this study that met the inclusion and exclusion criteria were then analyzed by bivariate test using the Pearson Chi-Square test. The findings from this study were stunted by as many as 55 respondents (61.1%). The study also found that more were getting exclusive breastfeeding as many as 55 respondents (61.1%). The incidence of stunting showed a higher proportion in infants aged 6-24 months without exclusive breastfeeding (p-value 0.001). This indicates that there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers at Kassi-Kassi Health Center.